1998
DOI: 10.1002/(sici)1097-0290(19980905)59:5<525::aid-bit1>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Influence of morphology and rheology on the production characteristics of the basidiomyceteCyathus striatus

Abstract: The influence of the pellet morphology of the basidiomycete Cyathus striatus on the production of the antibiotics striatals A, B, and C was investigated. The main operating parameters in fermenters of different sizes were the tip speed and the volumetric power input. Different methods were developed for quantification of morphological characteristics. The apparent viscosity of the suspension was measured with a cylinder rheometer. Sediment density was measured with a sedimentation apparatus. Particle size dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 14 publications
(19 reference statements)
1
25
0
1
Order By: Relevance
“…Several studies have shown that fermentation broths containing high concentrations of filamentous microorganisms are highly viscous and are characterized by shear-rate-dependent viscosities and by a yield stress (Ju et al 1991;Berovic et al 1993;Goudar et al 1999). In case of production, the yield is predicted by the measurement of the apparent viscosity of the culture in the production phase, and the morphological characteristics directly determine the rheological properties of the culture broth (Gehrig et al 1998). The non-Newtonian behavior is relatively predominant at lower shear rate and at higher mycelial concentration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that fermentation broths containing high concentrations of filamentous microorganisms are highly viscous and are characterized by shear-rate-dependent viscosities and by a yield stress (Ju et al 1991;Berovic et al 1993;Goudar et al 1999). In case of production, the yield is predicted by the measurement of the apparent viscosity of the culture in the production phase, and the morphological characteristics directly determine the rheological properties of the culture broth (Gehrig et al 1998). The non-Newtonian behavior is relatively predominant at lower shear rate and at higher mycelial concentration.…”
Section: Resultsmentioning
confidence: 99%
“…The rheological behavior is closely related to the morphology and biomass concentrations (Blanch and Bhavaraju 1976;Charles 1978;Metz et al 1979;Tucker and Thomas 1993). The broth rheology determines the transport phenomena in bioreactors and is considered to be the key factor for getting an improved yield of the targeted product (Berovic et al 1991;Gehrig et al 1998). Generally two types of growth forms the filamentous and pelleted can be observed during a fungal fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement procedure often is repeated for several samples, then the size distribution is calculated by averaging [82]. Furthermore, size distribution data have been linked with off-line data to plot the percent dry biomass versus pellet diameter [58] or to obtain the pellet density (division of dry cell weight by pellet volume), q p [28].…”
Section: Presentation and Analysis Of Bubble Size Distribution Datamentioning
confidence: 99%
“…Key quantities are the percentage of pellets [109] or the number frequency of pellets as function of size (e.g., radius) [86,103]. Other obtainable quantities include the pellet concentration, pellet volume (sum of individual particle volumes), average diameter (e.g., d a ), volume concentration (volume of pellets per liter of sample volume), cumulative volume concentration curve (addition of individual volume concentrations from 0 to d i ), normalized cumulative volume concentration curve (d max = 1), and median value of diameter, d 50 (diameter for which normalized cumulative volume curve is 0.5) [28].…”
Section: Presentation and Analysis Of Bubble Size Distribution Datamentioning
confidence: 99%
“…Leisola and Fiechter also reported that P. chrysosporium pellets with an average diameter of 0.1-0.2 cm produced the maximal lignin peroxidase activity (LiP) [16]. On the other hand there are investigations with basidiomycetes which state that the oxygen limitation in pellets can promote the secondary metabolite production [17][18][19].…”
Section: Microprofilingmentioning
confidence: 99%